Trends in Health Equity Among Children in the United States, 1997–2018 - Anderson, Nathaniel W.; Zimmerman, Frederick J. (Maternal and Child Health Journal, 2021)
Health equity is crucial to population health. To achieve this aim, extensive monitoring efforts beyond traditional disparities research are required. This analysis assesses trends in health equity for children from 1997 to 2018.